2021
DOI: 10.3390/antiox10060987
|View full text |Cite
|
Sign up to set email alerts
|

A New Geniposidic Acid Derivative Exerts Antiaging Effects through Antioxidative Stress and Autophagy Induction

Abstract: Two compounds that can prolong the replicative lifespan of yeast, geniposidic acid (Compound 1) and geniposide (Compound 2), were isolated from Gardenia jasminoides Ellis. Compared with Compound 1, Compound 2 was different at C11 and showed better bioactivity. On this basis, seven new geniposidic derivatives (3–9) were synthesized. Geniposidic 4-isoamyl ester (8, GENI), which remarkably prolonged the replicative and chronological lifespans of K6001 yeast at 1 µM, was used as the lead compound. Autophagy and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In this study, the expression of mTORC1, S6K1 and 4EBP1 was also significantly decreased with the downregulation of AiiMEK1, implying that mTOR regulatory signals can be reduced by inhibition of AiiMEK1 and postpone the senescence of A. irradians. The physiological process of autophagy can remove toxic and easily aggregated proteins to maintain the normal function of cells and thus prolong life (Melendez et al, 2003;Simonsen et al, 2008;Park and Kim, 2019;Wang et al, 2021). In this study, ULK1, a key gene in autophagy, was significantly lower in the MEK1 knock-down group than that in the control group, might suggest that autophagy is not largely involved in the bay scallops.…”
Section: Figure 11mentioning
confidence: 56%
“…In this study, the expression of mTORC1, S6K1 and 4EBP1 was also significantly decreased with the downregulation of AiiMEK1, implying that mTOR regulatory signals can be reduced by inhibition of AiiMEK1 and postpone the senescence of A. irradians. The physiological process of autophagy can remove toxic and easily aggregated proteins to maintain the normal function of cells and thus prolong life (Melendez et al, 2003;Simonsen et al, 2008;Park and Kim, 2019;Wang et al, 2021). In this study, ULK1, a key gene in autophagy, was significantly lower in the MEK1 knock-down group than that in the control group, might suggest that autophagy is not largely involved in the bay scallops.…”
Section: Figure 11mentioning
confidence: 56%
“…The previous study found that GPA protected the liver against D-galactosamine and lipopolysaccharide-induced hepatic failure in mice through increased NRF2/HO-1 expression levels [ 43 ]. Wang et al discovered that geniposidic acid and its derivative could prolong the replicative lifespan of K6001 yeast by reducing oxidative stress and inducing autophagy [ 44 ]. In this study, we found that GPA could efficiently reduce ROS while improving the viability of cell proliferation in H 2 O 2 -induced cells.…”
Section: Discussionmentioning
confidence: 99%
“…Selenite sulfide undergoes a reduction reaction with the second equivalent of GSH, regenerates into selenic acid, and then selenic acid enters the next cycle ( Figure 2 ), the entire catalytic reaction process is continuously carried out. In this process, the harmful peroxides in the organism are consumed, the content of active oxygen free radicals is reduced, and the cells are protected from oxidative damage, which is beneficial to the metabolic balance in the organism [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Natural Selenoenzymesmentioning
confidence: 99%